Implementasi Tanggung Jawab Sosial dan Lingkungan pada PT. Bali Pawiwahan (Coco Group) - SABATINA, VERONIKA; BUDIASA, I WAYAN; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Implementation of Social and Environmental Responsibility in PT Bali Pawiwahan (Coco Group) Corporate Social and Environmental Responsibility is a company or business world commitment to contribute to sustainable economic development which is strictly regulated in Indonesia through Law No. 40 of 2007 concerning Limited Liability Company, article 74 paragraph (1). The purpose of this study is to determine the proportion and the distribution of CSR funds at PT Bali Pawiwahan and also to identify to what extent the CSR implementation has fulfilled the CSR implementation regulations. This research was conducted at PT Bali Pawiwahan uses quantitative descriptive and qualitative descriptive data which were obtained from primary data and secondary data, the author conducted the key informant method. The methods of analysis used are quantitative descriptive and qualitative descriptive methods. The proportion of funds budgeted by the PT Bali Pawiwahan is 0.1% per year. The CSR program carried out by PT Bali Pawiwahan has fulfilled the regulations related to the implementation of social and environmental responsibility based on Law No.40, Article 74 of 2007 regarding Limited Liability Company. It is recommended that CSR activities are grouped into social, economic, and environmental categories, as well as the total budget spent in each of the main areas of CSR activities so that CSR report is more detailed and easier to understand.